Epidemiological Peculiarities of New Coronavirus Infection (COVID-2019). Communication 2: Peculiarities of epidemic process development in conjunction with performed anti-epidemic measures around the world and in the Russian Federation - V. V. Kutyrev; A. Yu. Popova; V. Yu. Smolensky; E. B. Ezhlova; Yu. V. Demina; V. A. Safronov; I. G. Karnaukhov; A. V. Ivanova; S. A. Shcherbakova (Проблемы особо опасных инфекций, 2020)
The review presents the analysis of the data on the spread of COVID-19 around the world and in Russia available as of June 15, 2020. Dynamics and geographical dissemination of COVID-19 in the Russian Federation is considered. The structure of incidence by gender and age is presented. Assessment of the key epidemiological parameters (morbidity rates and lethality) is provided. The effectiveness of the response measures conducted to control COVID-19 is discussed.